Globalising an Alternative Medical Knowledge: Modern and Transnational Ayurveda in Perspective - Harilal Madhavan
The study attempts to understand the transformation of Ayurvedic manufacturing in India with special reference to Kerala. It is contextualized in an ever-increasing demand for the herbal pharmaceuticals and related products all over the world as well as increasing initiatives for incorporating traditional knowledge in the development paradigms. Here, we explore how the early manufacturing in ayurvedic medical system has been evolved and how institutions have successfully promoted and incentivized the idea of manufacturing, which eventually led to modernization of the sector. It also endeavours to study the modern manufacturing practices, drug discovery process, innovation and contemporary intricacies of the sector includes, the inefficiency of incentive mechanisms. The prospects of the current growth have been analyzed within the institutional structure of the international agencies and policies of many export destination economies. In the process, we understand how ayurvedic knowledge system has been bifurcated and trifurcated and hence entered into various market segmentations, which so far unknown to the system. We understand the fact that the existence of medical pluralism, since the colonial time, now embedded with the phenomenon of pharmaceutical pluralism with the entry of ayurvedic products to the market. This development discourse is seen by the study as different points of confrontations of knowledge systems (power systems) namely colonial, postcolonial and post liberal, but in continuum. Information from secondary sources, archival materials, various government documents and primary close functional analyses and ethnographical understanding were used to complete this study and drawn methodological insights from various disciplines like economics, sociology and anthropology. Sociology of globalization, world system analysis and historical and comparative institutional analysis were blended to explain various explanatory points. In effect, the phenomenon of this transition of traditional health system was explained in the larger frame of globalization of knowledge